Transforming Relationships Between Israeli Settlers and West Bank Palestinians: Assessing the Case of “Roots” - Mollov, Ben; Lavie, Chaim (Journal of Leadership, Accountability and Ethics, 2020)
This article will present an advanced evaluation of “Roots” a cutting edge effort at dialogue and conflict resolution in the highly fraught area of the Israeli-Palestinian conflict between Israeli settlers and West Bank Palestinians. We present quantitative and qualitative empirical data to assess the impact of its main activities with reference to several important conflict resolution strategies. We assess that while its influence on the macro level is limited, Roots appears on the local level to be an effective agent to promote more civil and constructive interactions between Israelis and Palestinians, along with generating spill over effect into larger circles of influence for peace building.